Empirical Analysis of Production and Productivity of Indian Spices - Prakash, K. C.; Bhat, Pooja S.; Ganeshkumar, C. (Journal of Applied Business and Economics, 2022)
The aim of this paper is to compare the growth rate in the production as well as productivity of the King and Queen of spices i.e., Black Pepper and Cardamom in two states, Kerala and Karnataka which are the leading producers of spices in India, the paper makes use of secondary data. the article highlights that the spice growers are switching their crops from pepper to cardamom and other plants. This can be caused by the reduction in productivity of pepper, and also in general, pepper cannot be grown as cardamom or paddy again on the same piece of land. Besides, the pepper price fluctuation is smaller than cardamom and other crops. However, the decrease in pepper productivity is above the degree of pepper price stability and this study highlights the plantation sector, more specifically, spices which contribute largely to the Indian economy, and which is often an underutilized sector despite its vast potential.